Viral encephalitis - Marcus Tulius T Silva (Arquivos de Neuro-Psiquiatria)
While systemic viral infections are exceptionally common, symptomatic viral infections of the brain parenchyma itself are very rare, but a serious neurologic condition. It is estimated that viral encephalitis occurs at a rate of 1.4 cases per 100.000 inhabitants. Geography is a major determinant of encephalitis caused by vector-borne pathogens. A diagnosis of viral encephalitis could be a challenge to the clinician, since almost 70% of viral encephalitis cases are left without an etiologic agent identified. In this review, the most common viral encephalitis will be discussed, with focus on ecology, diagnosis, and clinical management.